2008
DOI: 10.1159/000151726
|View full text |Cite
|
Sign up to set email alerts
|

The Composition of Bovine Peritubular Dentin: Matching TOF-SIMS, Scanning Electron Microscopy and Biochemical Component Distributions

Abstract: Peritubular dentin (PTD) is a hypermineralized phase within the dentinal tubules in some vertebrate teeth as an interface between the intertubular dentin (ITD) and the cell processes. Our aim has been to understand the composition, structure and role of PTD as a mineralized tissue. We have utilized the technique of time of flight secondary ion mass spectrometry (TOF-SIMS) to map the distribution of positive and negative inorganic ions as well as organic components in the fully mineralized, intact PTD structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 25 publications
3
26
0
1
Order By: Relevance
“…Similar results were obtained in some other studies [15,18,24]. The overall Mg concentrations reported for canine, equine, and human dentin are 1.545% [41], 0.63% in PTD and 0.56% in ITD [25], and 0.858% [42], respectively.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Similar results were obtained in some other studies [15,18,24]. The overall Mg concentrations reported for canine, equine, and human dentin are 1.545% [41], 0.63% in PTD and 0.56% in ITD [25], and 0.858% [42], respectively.…”
Section: Discussionsupporting
confidence: 88%
“…Atoms with higher atomic number appear brighter and those with lower atomic number darker. In dentin brighter PTD indicates mainly higher concentration of Ca and P ions and thus a higher degree of mineralization comparing to darker ITD [14,18,25]. As expected, EDXS measurements of PTD and ITD confirmed that the main dentin constitutive elements were Ca and P. Interestingly, in all species investigated higher amounts of P were assigned in PTD compared to ITD.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…For some time, dentin tissue has been extensively analyzed by means of scanning electron microscopy, and in the published studies details of new dentinal structures were described (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). In 1964, Scott (24) described that OPs in the inner third of the dentin were associated with thin fibrils and thought they were OP ramifications.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to enamel, dentine consists of a larger variety of proteins [Linde, 1989;Fujisawa and Kuboki, 1990;Linde and Goldberg, 1993], where linkages to the mineral appear to arise from acidic non-collagenous proteins [Boskey, 1989;Butler and Ritchie, 1995;Duer et al, 2009;Iline et al, 2015]. Linkages have also been reported to involve glutamic acid-rich protein of high-molecular-mass calcium-proteolipid-phospholipid-phosphate complexes elucidated by time-of-flight secondary ion mass spectrometry (ToF-SIMS) [Gotliv and Veis, 2009].…”
mentioning
confidence: 99%